2013
DOI: 10.1155/2013/605931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propofol on Acid Reflux Measured with the Bravo pH Monitoring System

Abstract: Background/Aim. The aim of this study was to determine the effect of propofol on acid reflux as measured with the Bravo pH monitoring system. Methods. 48-hour pH tracings of 88 children were retrospectively evaluated after placement of the Bravo capsule under propofol. Comparisons between day 1 and day 2, as well as 6-hour corresponding segments from day 1 and day 2, were made. Results. The number of reflux episodes was significantly increased during the first six-hour period on day one as compared to day 2 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…Similar to the Bravo probe study, 12 our study found increased acid refluxes per hour and total reflux per hour following placement of the probe. However, we also found a significant change over time in the non-acid refluxes per hour in the no sedation group which was not statistically significant in the anesthesia group, contrary to what we had hypothesized.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to the Bravo probe study, 12 our study found increased acid refluxes per hour and total reflux per hour following placement of the probe. However, we also found a significant change over time in the non-acid refluxes per hour in the no sedation group which was not statistically significant in the anesthesia group, contrary to what we had hypothesized.…”
Section: Discussionsupporting
confidence: 87%
“…12 This study found increased reflux episodes in the period following anesthesia, but evaluated only pH and not impedance. In this study, the attachment of the capsule itself may alter reflux patterns.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Potential disadvantages include additional expense due to endoscopic placement (as na-sal passage can be difficult due to size of capsule), early detachment in a minority of patients, patient discomfort which could require removal via repeat endoscopy, as well as overdiagnosis of GERD due to ingestion of acidic foods [16] . There is also some data suggesting an increased number of reflux episodes during the first 6 hour period following propofol administration [17] .…”
Section: Ambulatory Ph Monitoringmentioning
confidence: 99%
“…Potential disadvantages include additional expense due to endoscopic placement (as nasal passage can be difficult due to size of capsule), early detachment in a minority of patients, patient discomfort which could require removal via repeat endoscopy, as well as overdiagnosis of GERD due to ingestion of acidic foods [16] . There is also some data suggesting an increased number of reflux episodes during the first 6 hour period following propofol administration [17] . Transnasal catheter pH testing is limited by patient tolerance and 24 h monitoring but has the unique advantage of adding impedance which allows distinguishing between acid and non-acid (weakly acidic or weakly alkaline) gastroesophageal reflux.…”
Section: Ambulatory Ph Monitoringmentioning
confidence: 99%